Mechanism of interaction between TTR tetramer and Aβ42 oligomers: Dependence on the Aβ42 oligomeric size and morphology - Jinfei Mei; Wenqi Gao; Yvning Guan; Sajjad Ahmad; Fahad Nouman Muhammad; Hongqi Ai (ChemPhysMater)
β-amyloid (Aβ) deposits are the leading cause of Alzheimer's disease. Many studies have confirmed that transthyretin (TTR) inhibits the cytotoxicity of Aβ oligomers (AβOs) with various species (oligomers and protofibrils, but not monomers) through their interactions. Here, we investigated the mechanisms of interactions between the TTR tetramer and various Aβ species, including two monomers with different morphologies and four oligomers with different molecular weights, by employing molecular dynamics simulations. From these results, we propose a clear interaction scenario: upon AβO binding, the dimer−dimer distance of TTR increases and the binding energy decreases, indicating an unfavorable effect on the TTR stability. Moreover, the larger the molecular weight (MW) of AβO, the greater the effect of interaction between the TTR tetramer and Aβ oligomer, and consequently the worse the TTR stability. In turn, Aβ–Aβ intermolecular distances in AβO grow and the hydrophobic solvent-accessible surface area (SASA) increases, whereas the number of intermolecular hydrogen bonds decreases, indicating AβO disaggregation induced by the TTR binding. Moreover, a trend is observed for the disaggregation to increase as the MW of the AβO species increases. Finally, we reveal that conformations rich in helical sections rather than the semi-extended conformation are favored upon binding with TTR. Overall, this study provides a comprehensive molecular-level insight to better understand the mechanism and principles of interaction between the TTR tetramer and AβOs.